Effects of pneumonectomy on nitric oxide synthase expression and perivascular edema in the remaining lung of rats - Samano,M.N. (2009)
Pneumonectomy is associated with high mortality and high rates of complications. Postpneumonectomy pulmonary edema is one of the leading causes of mortality. Little is known about its etiologic factors and its association with the inflammatory process. The purpose of the present study was to evaluate the role of pneumonectomy as a cause of pulmonary edema and its association with gas exchange, inflammation, nitric oxide synthase (NOS) expression and vasoconstriction. Forty-two non-specific pathogen-free Wistar rats were included in the study. Eleven animals died during or after the procedure, 21 were submitted to left pneumonectomy and 10 to sham operation. These animals were sacrificed after 48 or 72 h. Perivascular pulmonary edema was more intense in pneumonectomized rats at 72 h (P = 0.0131). Neutrophil density was lower after pneumonectomy in both groups (P = 0.0168). There was higher immunohistochemical expression of eNOS in the pneumonectomy group (P = 0.0208), but no statistically significant difference in the expression of iNOS. The lumen-wall ratio and pO2/FiO2 ratio did not differ between the operated and sham groups after pneumonectomy. Left pneumonectomy caused perivascular pulmonary edema with no elevation of immunohistochemical expression of iNOS or neutrophil density, suggesting the absence of correlation with the inflammatory process or oxidative stress. The increased expression of eNOS may suggest an intrinsic production of NO without signs of vascular reactivity.